Nirwasita: Ponggalan Village Learning Center (Ex-Localization of Giwangan) Towards an Empowered and Achievement Community - Putro, Bayu Anggoro; Hermawan, Yudan; Habibah, Ju Linda; Ramadani, Diah Putri (Program Studi Pendidikan Luar Sekolah FKIP Universitas Jember, 2024)
Central Statistics Agency (BPS) In 2022, the crime rate for Yogyakarta City was recorded at 736 cases and the Giwangan area was the area contributing the largest cases. This number has increased from the previous year of 633 cases. Apart from that, the village has a waste problem that must be resolved immediately. Education is one solution in dealing with these cases. Through innovation, students can strengthen growth, impact, awareness and teamwork to support the management of village resources towards empowered and achieving villages. Nirwasita is a superior innovation to solve problems in Ponggalan Village. Nirwasita is a community learning center which has the following objectives: a). Striving for access, quality, and self-awareness; B). Reading new skills for the people of Ponggalan Village through entrepreneurship training. Nirwasita offers solutions through: a). Increasing knowledge and character using the digital corner, literacy corner and hope corner methods; B). Improving skills by using the work corner.